Pickering emulsions stabilized by β-CD microcrystals: Construction and interfacial assembly mechanism - Kou, Xingran; Zhang, Xinping; Ke, Qinfei; Meng, Qingran (Frontiers in Nutrition, 2023)
β-cyclodextrin (β-CD) can combined with oil and other guest molecules to form amphiphilic inclusion complexes (ICs), which can be adsorbed on the oil-water interface to reduce the interfacial tension and stabilize Pickering emulsion. However, the subtle change of β-CD in the process of emulsion preparation is easily ignored. In this study, β-CD and ginger oil (GO) were used to prepare Pickering emulsion by high-speed shearing homogenization without exogenous emulsifier. The stability of the emulsion was characterized by microscopic observation, staining analysis and creaming index (CI). Results showed that the flocculation of the obtained Pickering emulsion was serious, and the surface of the droplets was rough with lamellar particles. In order to elucidate the formation process of the layered particles, the GO/β-CD ICs was further prepared by ball milling method, and the X-ray diffraction (XRD), scanning electron microscopes (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and interfacial tension analyses found that β-CD and GO first formed amphiphilic nanoscale small particles (ICs) through the host-guest interaction, and the formed small particles were further self-assembled into lamellar micron-scale amphiphilic ICs microcrystals. These amphiphilic ICs particles and microcrystals could aggregate at the oil-water interface, and finally form Pickering emulsion. In this study, by exploring the formation process and evolution of GO/β-CD self-assembly, the formation process and stabilization mechanism of β-CD stabilized GO Pickering emulsion were clarified preliminarily, hoping to provide a theoretical basis for the development of high-performance CDs stabilized Pickering emulsions.